Cybercrusaders. - CHIN-CHIN YAP (ArtAsiaPacific)
An essay is presented concerning the field of computer hacker art. It discusses the organization the Electronic Disturbance Theater (EDT) and its computer application known as FloodNet, Italian conceptual artist Paolo Cirio and his project "Loophole for All," and the group known as Ubermorgen. The article examines how governments and legal authorities treat hacker art and hacker artists and how hacker artists expose security flaws in computer systems.